2020
DOI: 10.1029/2019wr026085
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Predictive Skill of a Distributed Hydrological Model by Calibration on Spatial Patterns With Multiple Satellite Data Sets

Abstract: Hydrological model calibration combining Earth observations and in situ measurements is a promising solution to overcome the limitations of the traditional streamflow-only calibration. However, combining multiple data sources in model calibration requires a meaningful integration of the data sets, which should harness their most reliable contents to avoid accumulation of their uncertainties and mislead the parameter estimation procedure. This study analyzes the improvement of model parameter selection by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 187 publications
3
74
0
2
Order By: Relevance
“…The model is calibrated only on Q data despite the known limitations of the Q-only calibration (Demirel et al, 2018). However, calibrating the model on additional variables would result in additional model performance improvement that would not be separable from the contribution of the input datasets to the model performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model is calibrated only on Q data despite the known limitations of the Q-only calibration (Demirel et al, 2018). However, calibrating the model on additional variables would result in additional model performance improvement that would not be separable from the contribution of the input datasets to the model performance.…”
Section: Discussionmentioning
confidence: 99%
“…A dynamical scaling function (F DS ) (cf. Demirel et al, 2018) is used to account for vegetation-climate interactions (Bai et al, 2018;Jiao et al, 2017). E p is formulated as follows:…”
Section: Hydrological Model Set-upmentioning
confidence: 99%
“…Several studies have shown that streamflow, being an integrative response of the entire watershed, cannot adequately inform the spatial representation of ET and SM [37,38]. Recent studies have shown that using the spatial structure of ET and SM from remote sensing data along with streamflow data in calibration can produce physically consistent estimates of all the components [9,39,40]. In this regard, our study agrees with the findings of the hydrologic modeling community, with the spatial RMSE plots (Figure 4), variograms, and correlograms ( Figure 5) showing that considering ET and SM moisture improves their spatial structure.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate calibration of hydrologic models is generally carried out by combining different hydrologic variables into a single objective function by using weights [9,40,41]. Such an approach makes it difficult to analyze the trade-offs in accuracy among the different variable involved.…”
Section: Discussionmentioning
confidence: 99%
“…This study analysis the future evolution of the spatiotemporal dynamics of multiple hydrological processes (i.e. streamflow, soil moisture, evaporation and terrestrial water storage) with the fully distributed mesoscale hydrologic Model (mHM), which is constrained with a novel multivariate calibration approach based on the spatial patterns of satellite remote sensing data (Dembélé et al, 2020). The experiment is done in the large and transboundary Volta River Basin (VRB) in West Africa, which is a hotspot of climate vulnerability.…”
mentioning
confidence: 99%